2021
DOI: 10.1007/s00167-021-06732-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative rotator cuff tendon integrity, tear size, and muscle atrophy and fatty infiltration are associated with structural outcomes of arthroscopic revision rotator cuff repair

Abstract: PurposeA few studies have focused on factors predisposing to retear after arthroscopic revision rotator cuff repair (ARRCR). This study aimed to retrospectively evaluate (1) the structural and clinical outcomes of ARRCR and (2) pre‐ and intraoperative factors affecting the integrity of the rotator cuff (RC) tendon by focusing on preoperative RC tendon integrity, tear size, muscle hypotrophy and fatty infiltration. MethodsPatients who underwent ARRCR between 2006 and 2016 were reviewed. Preoperative variables i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…Our data demonstrate that 3D muscle volumetry should be preferred in patients with full-thickness SSP tendon tears when the muscle volume needs to be quantified preoperatively in order to estimate the postoperative success rate after tendon repair procedures. This is in accordance with previous studies [ 17 ] and is important since various previous experimental and clinical studies have shown that significant SSP muscle atrophy is an important adverse prognostic factor affecting patients’ outcomes in addition to other conditions, e.g., fatty infiltration or severe tear size [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrate that 3D muscle volumetry should be preferred in patients with full-thickness SSP tendon tears when the muscle volume needs to be quantified preoperatively in order to estimate the postoperative success rate after tendon repair procedures. This is in accordance with previous studies [ 17 ] and is important since various previous experimental and clinical studies have shown that significant SSP muscle atrophy is an important adverse prognostic factor affecting patients’ outcomes in addition to other conditions, e.g., fatty infiltration or severe tear size [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…As an important predictor of repair integrity, the overall fatty degeneration of RC muscles greatly influences postoperative shoulder strength and functional outcomes. 7,16,18 Thus, accurate and reliable evaluations of the Global-FI in the RC muscles are meaningful for appropriate treatment decision making and prognosis. 32 In clinical practice, a qualitative grading system, such as the Goutallier or Fuchs classification based on a single CT or MRI scan, has been widely used for assessing FI, aiming to view a single image as a predictor of the entire degenerative features throughout the RC.…”
Section: Discussionmentioning
confidence: 99%
“…13,22 The overall rotator cuff (RC) muscle fatty degeneration correlates with limited shoulder motion, decreased postoperative strength, and retear. 7,16,18 In this context, an accurate and repeatable assessment of the global RC muscle FI is imperative to help determine the most appropriate treatment options and prognosis and is a prerequisite for communication between doctors for appropriate decision making.…”
mentioning
confidence: 99%
“…Previous literature has reported that preoperative RC tear size and fatty infiltration are associated with tendon integrity and risk of retear after RCR. 12 , 22 , 26 Although somewhat counterintuitive, research has demonstrated a disconnect between imaging findings of RC disease and patients’ subjective experience of shoulder pain and function, 35 which may explain the present findings. Alternatively, it is possible that the PROMIS–UE questionnaire is not sensitive enough for the assessment of shoulder-specific recovery after RCR.…”
Section: Discussionmentioning
confidence: 58%